Ética profesional y satisfacción del rol institucional en profesionales contables de la región Loreto año 2025 - Bustos Cerdeira, Joyrathi Hypathia Coraima (2025)
The lack of modernization and prominence of the College of Accountants of Loreto has generated disinterest and low participation of accountants, weakening their representation and professional influence in the region, for this reason, the purpose of this study is to identify how professional ethics and satisfaction with the institutional role of the College of Public Accountants are presented in accounting professionals in the Loreto region in 2025, from a quantitative approach, observational and descriptive non-experimental design, considering as the study population the licensed Public Accountants of the city of Iquitos, which are estimated to be 1,259. The results revealed that professional ethics were valued widely positively, with more than 95% of respondents. Among the most notable aspects are the confidentiality of information, honesty, respect for standards and equity, reflecting a solid internalization of ethical principles in the accounting practice. Regarding satisfaction with the institutional role of the College of Accountants, the results were favorable, especially in relation to the The study identified more moderate levels of satisfaction regarding professional association support and social benefits. It concluded that certified public accountants in Loreto maintain a strong commitment to ethical principles and value the role of the Association in their training and professional development. However, it also highlights the need to strengthen institutional actions that reinforce the sense of professional association support and the perception of tangible benefits.